Pulmonary Veno-Occlusive Disease: A Rare Cause of Pulmonary Hypertension - Said Hajouli MD; Muhamad Alhaj Moustafa MD; Jessica S. Wang Memoli MD (SAGE Publishing, 2019)
Pulmonary veno-occlusive disease (PVOD) is a rare entity that is usually mistaken with pulmonary arterial hypertension (PAH) but is considered class I' of PAH. It is important to subclassify PVOD and distinguish it from PAH as treatment with vasodilators in PVOD patients is controversial and may be fatal. In this article, we describe a case of PVOD and how we diagnosed it.